Exploring Vertical Transmission of Bifidobacteria from Mother to Child - Milani, Christian (Appl Environ Microbiol, 2015)
Passage through the birth canal and consequent exposure to the mother's microbiota is considered to represent the initiating event for microbial colonization of the gastrointestinal tract of the newborn. However, a precise evaluation of such suspected vertical microbiota transmission has yet to be performed. Here, we evaluated the microbiomes of four sample sets, each consisting of a mother's fecal and milk samples and the corresponding infant's fecal sample, by means of amplicon-based profiling supported by shotgun metagenomics data for two key samples. Notably, targeted genome reconstruction from microbiome data revealed vertical transmission of a Bifidobacterium breve strain and a Bifidobacterium longum subsp. longum strain from mother to infant, a notion confirmed by strain isolation and genome sequencing. Furthermore, PCR analyses targeting unique genes from these two strains highlighted their persistence in the infant gut at 6 months. Thus, this study demonstrates the existence of specific bifidobacterial strains that are common to mother and child and thus indicative of vertical transmission and that are maintained in the infant for at least relatively short time spans.